Acinetobacter lactucae Strain QL-1, a Novel Quorum Quenching Candidate Against Bacterial Pathogen Xanthomonas campestris pv. campestris - Ye, Tian; Zhou, Tian; Fan, Xinghui; Bhatt, Pankaj; Zhang, Lianhui; Chen, Shaohua (Frontiers in Microbiology, 2019)
Quorum sensing (QS) is a cell-cell communication mechanism among bacterial populations that is regulated through gene expression in response to cell density. Pathogenicity of Xanthomonas campestris pv. campestris (Xcc) is modulated by the diffusible signal factor (DSF)-mediated quorum sensing system. DSF is widely conserved in a variety of gram-negative bacterial pathogens. In this study, DSF-degrading bacteria and their enzymes were thoroughly explored as a biocontrol agent against Xcc. Results indicated that a novel DSF-degrading bacteria Acinetobacter lactucae QL-1 effectively attenuated Xcc virulence through quorum quenching. Lab-based experiments indicated that plants inoculated with QL-1 and Xcc had less tissue decay compared to inoculation with Xcc alone. Co-inoculation of strains Xcc and QL-1 significantly reduced the disease incidence and severity in plants. Similarly, the application of crude enzymes of strain QL-1 substantially reduced the disease severity caused by Xcc. The results showed that strain QL-1 and its enzymes possess promising potential, which could be further investigated to better protect plants from DSF-dependent pathogens.